Purification of the key enzyme complexes of the anammox pathway from DEMON sludge. Issue 6 (2nd April 2021) - Akram, Mohd; Dietl, Andreas; Müller, Melanie; Barends, Thomas R. M.
Abstract: Anaerobic Ammonium Oxidation ("anammox") is a bacterial process in which nitrite and ammonium are converted into nitrogen gas and water, yielding energy for the cell. Anammox is an important branch of the global biological nitrogen cycle, being responsible for up to 50% of the yearly nitrogen removal from the oceans. Strikingly, the anammox process uniquely relies on the extremely reactive and toxic compound hydrazine as a free intermediate. Given its global importance and biochemical novelty, there is considerable interest in the enzymes at the heart of the anammox pathway. Unfortunately, obtaining these enzymes in sufficiently large amounts for biochemical and structural studies is problematic, given the slow growth of pure cultures of anammox bacteria when high cell densities are required. However, the anammox process is being applied in wastewater treatment to remove nitrogenous waste in processes like DEamMONification (DEMON). In plants using such processes, which rely on a combination of aerobic ammonia‐oxidizers and anammox organisms, kilogram amounts of anammox bacteria‐containing sludge are readily available. Here, we report a protein isolation protocol starting from anammox cells present in DEMON sludge from a wastewater treatment plan that readily yields pure preparations of key anammox proteins in the tens of milligrams, including hydrazine synthase HZS and hydrazine dehydrogenase (HDH), as well as hydroxylamine oxidoreductase (HAO). HDH and HAO were active and of sufficient quality for biochemical studies and for HAO, the crystal structure could be determined. The method presented here provides a viable way to obtain materials for the study of proteins not only from the central anammox metabolism but also for the study of other exciting aspects of anammox bacteria, such as for example, their unusual ladderane lipids. Abstract :